Factors influencing mobile learning technology adoption and learning outcomes in online piano education: A comparative study of Chinese and Russian students - Baiyu Chen; Rongyi Tang (PLoS ONE, 2025)
Mobile learning technologies (MLTs) have opened new opportunities for enhancing piano education, yet factors influencing their adoption and impact on learning outcomes remain largely unexplored. This study investigates how prior domain-specific knowledge, prior experience with technology-mediated learning, and self-efficacy influence piano learners’ adoption of MLTs and examines the relationship between MLT adoption and learning outcomes. A cross-sectional survey design was employed with university music students from China and Russia (N = 240; 120 in China, 120 in Russia). Data were collected using a 5-point Likert questionnaire of 20 items measuring the study constructs. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data. All hypothesized relationships were supported across both cultural contexts. Prior domain-specific knowledge (β = 0.547, p < 0.001), prior experience with technology-mediated learning (β = 0.638, p < 0.001), and self-efficacy (β = 0.639, p < 0.001) significantly influenced MLT adoption. MLT adoption positively impacted learning outcomes (β = 0.541, p < 0.001). Effect sizes ranged from medium to large (f² = 0.26–0.35). No significant differences were found between Chinese and Russian students, suggesting cross-cultural applicability. The findings demonstrate MLTs’ potential to support piano education globally by providing flexible, accessible, and interactive learning experiences. Results highlight the importance of considering learners’ prior knowledge, technology experience, and self-efficacy when implementing mobile learning solutions. This represents the first cross-cultural PLS-SEM study of piano MLT adoption, providing empirical evidence for technology integration in music pedagogy.